Effect of beraprost on pulmonary hypertension due to left ventricular systolic dysfunction - Wang, Li (Medicine (Baltimore), 2019)
Beraprost is used to treat peripheral chronic arterial occlusive disease. However, the efficacy and safety of beraprost in patients with pulmonary hypertension (PH) due to left ventricular systolic dysfunction (PH-HFrEF) remains unknown. The primary objective of this study was to determine the effects of beraprost on PH-HFrEF. We prospectively recruited patients with PH-HFrEF as determined by echocardiography and right cardiac catheterization. Beraprost sodium was given orally (1 μg/kg/d) added to the usual treatment, and patients were evaluated at 1-year follow-up. Twenty-five patients were recruited with baseline systolic pulmonary artery pressure (PAP) of 49.5 ± 10.8 mm Hg. Systolic PAP results at 3, 6, 9, and 12 months were 39.1 ± 8.1, 30.4 ± 5.2, 27.7 ± 3.0, and 27.0 ± 4.7 mm Hg, respectively, which were all significantly lower than systolic PAP at baseline (P < .05). Left ventricular ejection fraction results at 6 months (43.5 ± 7.0%), 9 months (47.0 ± 5.5%), and 12 months (48.2 ± 4.8%) were significantly higher than at baseline (34.7 ± 9.2%) (P < .05). Six-minute walking distance at 3 months (282.8 ± 80.6 m), 6 months (367.1 ± 81.2 m), 9 months (389.8 ± 87.1 m), and 12 months (395.7 ± 83.4 m) increased with time, and all were significantly higher than baseline (190.1 ± 75.5 m) (P < .05). One patient developed atrial fibrillation and recovered to sinus rhythm after intravenous administration of amiodarone. There were no instances of cardiac-related death, severe bleeding, or severe impairment of liver function. Routine oral administration of beraprost sodium added to the usual treatment may improve cardiopulmonary hemodynamics and exercise capacityin patients with PH-HFrEF.